2021
DOI: 10.1093/fampra/cmab033
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between duration and quality of sleep and upper respiratory tract infections: a systematic review

Abstract: Background Upper respiratory tract infections (URTIs) are common, mostly self-limiting, but result in inappropriate antibiotic prescriptions. Poor sleep is cited as a factor predisposing to URTIs, but the evidence is unclear. Objective To systematically review whether sleep duration and quality influence the frequency and duration of URTIs. Methods Three data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The UK Biobank has received approval as a Research Tissue Bank from the North West Multicentre Research Ethics Committee (MREC) under MREC permits 11/NW/0382 (2011-2016), 16/NW/0274 (2016-2021) and 21/NW/0157 (2021-2026). Researchers with approved applications are covered by these permits and are not required to seek additional approval, except in specific cases (see section B7 of the UK Biobank Access Procedures document: https://www.ukbiobank.ac.uk/media/omtl1ie4/access-procedures-2011-1.pdf).…”
Section: Uk Biobankmentioning
confidence: 99%
See 1 more Smart Citation
“…The UK Biobank has received approval as a Research Tissue Bank from the North West Multicentre Research Ethics Committee (MREC) under MREC permits 11/NW/0382 (2011-2016), 16/NW/0274 (2016-2021) and 21/NW/0157 (2021-2026). Researchers with approved applications are covered by these permits and are not required to seek additional approval, except in specific cases (see section B7 of the UK Biobank Access Procedures document: https://www.ukbiobank.ac.uk/media/omtl1ie4/access-procedures-2011-1.pdf).…”
Section: Uk Biobankmentioning
confidence: 99%
“…In contrast, large cohort studies of poor sleep have shown that chronic sleep loss and insomnia are associated with increased rates of both all-cause mortality 13,14 and viral infection 15 . More recently, a review of nine small-scale studies that assessed the effect of chronic short and long sleep on risk of developing respiratory infections 16 , found that short sleep was associated with an increased overall risk of respiratory infections (HR = 1.30 [1.19, 1.42], P<1×10 −5 ). Evidence collected from a number of cross-sectional studies also points to insomnia being associated with an increased prevalence of respiratory infections 17 , though cause and effect is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Considering other pillars of Lifestyle Medicine, sleep deprivation and cortisol (released upon stress) both supress immune function. A systematic review associated <7 h sleep/night with a 31% increased risk of upper respiratory tract infections (with the obvious caveat that activities limiting sleep duration may have contributed) 9 . Meanwhile, a prospective cohort study correlated psychological distress during the early pandemic with subsequent infection risk and symptom severity 10 .…”
Section: The Influence Of Lifestyle Behaviours On Covid‐19 Infection ...mentioning
confidence: 99%
“…This dual sleep and circadian rhythm disruption (SCRD) is often encountered by shift workers, particularly those working at night, and is a well-established risk factor for respiratory viral infections. The common cold 52 , Influenza 6,7,26 , and indeed upper respiratory viral infections in general 8,10 are all significantly increased following SCRD. The recent global research effort on SARS-CoV-2 has resulted in multiple studies reporting an association between shift work, sleep disruption and the risk of developing severe COVID-19 12,[14][15][16]53 .…”
Section: Introductionmentioning
confidence: 98%
“…An increased understanding of the risk factors and mechanisms driving severe respiratory disease will inform new treatment options. Sleep and circadian disruption have been reported to cause an increased risk of respiratory infections in mice and humans [6][7][8][9][10] and accumulating evidence suggests that shift work and the associated sleep deprivation and circadian rhythm misalignment are risk factors for COVID-19 [11][12][13][14][15][16] . Yet, a mechanistic explanation of how sleep and circadian disruption causes higher rates of viral infections remains to be determined.…”
Section: Introductionmentioning
confidence: 99%